2012
DOI: 10.1111/j.1751-7893.2011.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Social functioning in early psychosis: are all the domains predicted by the same variables?

Abstract: Results suggest that negative symptoms are predictive of all three areas of functioning but that specific variables add significant unique variance to individual areas of social functioning. Although a global social functioning score can be considered useful, greater precision can be gained by the use of domain-specific measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…This is especially true for positive symptoms. In concordance with the literature, the present analyses show that negative symptoms are more consistently related to both current (Chang et al, 2011;Bourdeau et al, 2012;Evensen et al, 2012a,b) and future levels (Albert et al, 2011;Álvarez-Jiménez et al, 2012;Vesterager et al, 2012;González-Ortega et al, 2013) of psychosocial functioning than positive symptoms (Albert et al, 2011;Faber et al, 2011;Ventura et al, 2011;Chang et al, 2012). Also, severity levels of both positive and negative symptoms do not appear to be strong predictors of psychosocial functioning after 12 months (Albert et al, 2011;Faber et al, 2011;Chang et al, 2012).…”
Section: Comparison With Earlier Studiessupporting
confidence: 90%
“…This is especially true for positive symptoms. In concordance with the literature, the present analyses show that negative symptoms are more consistently related to both current (Chang et al, 2011;Bourdeau et al, 2012;Evensen et al, 2012a,b) and future levels (Albert et al, 2011;Álvarez-Jiménez et al, 2012;Vesterager et al, 2012;González-Ortega et al, 2013) of psychosocial functioning than positive symptoms (Albert et al, 2011;Faber et al, 2011;Ventura et al, 2011;Chang et al, 2012). Also, severity levels of both positive and negative symptoms do not appear to be strong predictors of psychosocial functioning after 12 months (Albert et al, 2011;Faber et al, 2011;Chang et al, 2012).…”
Section: Comparison With Earlier Studiessupporting
confidence: 90%
“…Terms such as social functioning are used interchangeably with terms such as social adjustment, adaptation, dysfunction, competence and quality of life, and scales of measurement are also used interchangeably [58]. Combining all indices of functioning under the umbrella term 'psychosocial outcome' may also be problematic, as predictors may be differentially associated with specific functional domains [20,34]. Moreover, quantifying good psychosocial outcome is difficult given the value judgments involved because it differs by culture and individual [57].…”
Section: Resultsmentioning
confidence: 99%
“…More recently, there has been increasing interest in the study of social cognition and social functioning in first‐episode psychosis (FEP) (Addington, Saeedi, & Addington, ; Thompson et al, ). Available research suggests that deficits in both of these variables are present early in the course of psychotic disorders (Achim, Ouellet, Roy, & Jackson, ; Bourdeau, Masse, & Lecomte, ; Lecomte et al, ; Thompson et al, ) and may also be present in first‐degree relatives of individuals with psychotic disorders (Glatt, Stone, Faraone, Seidman, & Tsuang, ; Lavoie, Bédard Lacroix, Godmaire‐Duhaime, Jackson, & Achim, ). Individuals early in the course of a psychotic illness may also be more responsive to psychosocial interventions than individuals with longstanding psychotic disorders (Goldstein, ; McFarlane, )—a finding that may be particularly relevant to recent efforts to develop psychosocial interventions to address social cognitive deficits in psychosis (Bartholomeusz et al, ; Penn, Roberts, Combs, & Sterne, ; Roberts & Penn, ).…”
Section: Introductionmentioning
confidence: 99%
“…Available research suggests that deficits in both of these variables are present early in the course of psychotic disorders (Achim, Ouellet, Roy, & Jackson, 2012;Bourdeau, Masse, & Lecomte, 2012;Lecomte et al, 2014;Thompson et al, 2012) and may also be present in firstdegree relatives of individuals with psychotic disorders (Glatt, Stone, Faraone, Seidman, & Tsuang, 2006;Lavoie, Bédard Lacroix, Godmaire-Duhaime, Jackson, & Achim, 2013). Individuals early in the course of a psychotic illness may also be more responsive to psychosocial interventions than individuals with longstanding psychotic disorders (Goldstein, 1996;McFarlane, 2002)-a finding that may be particularly relevant to recent efforts to develop psychosocial interventions to address social cognitive deficits in psychosis (Bartholomeusz et al, 2013;Penn, Roberts, Combs, & Sterne, 2007;Roberts & Penn, 2009 (Green et al, 2008) identified 5 domains of social cognition relevant to the study of psychotic disorders (ie, attributional style, emotion recognition, social knowledge, social perception and theory of mind), no study to date has examined all 5 domains of social cognition simultaneously in the same sample (Addington & Piskulic, 2011;Thompson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation